PERUBAHAN BELAJAR SAINS SISWA SEKOLAH DASAR PADA PEMBELAJARAN TERINTEGRASI (TERPADU) MELALUI MODEL DISCOVERY LEARNING - Yanti Fitria (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was toinvestigate the effect of Discovery Learning  model on student learning outcomes on the theme Object Around Usat 5th grade of Elementary School integrated thematic learning. This research is a quantitative research with quasi experimental research design. The population of this research is the students of 5th grade of elementary school in Region Six Garegeh of Bukittinggi City. The sample of this research is the 5th grade students of SDN 04 Garegeh consisting of two classes with the number of students VA class is 33 students and VB class is 32 students. Sampling was done by random sampling. Based on the research that has been done, obtained tcount> ttable that is 7,185 > 1,998 with α = 0,05 so it can be concluded Ha accepted that there is influence the use of Discovery Learning model of student learning outcomes. Keyword : Discovery Learning model, learning outcomes